2019
DOI: 10.4314/nvj.v40i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Geo-spatial distribution of <i>Brucella melitensis</i> infection in selected local government areas of Katsina and Sokoto States, Nigeria

Abstract: Brucellosis due to Brucella melitensis infects mostly small ruminants and has been reported to be the most invasive and pathogenic species for humans. A cross-sectional sero-geospatial study was conducted in 4 and 3 Local Government Areas (LGAs) of Katsina and Sokoto States, Nigeria respectively. Sera were analysed using c-ELISA while A Global Positioning System (GPS) receiver was used to take geographic coordinates of all sampling points. Data were analysed with SPSS version 20. Chi-square test was used to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The documentation of geospatial distribution of B. abortus infection in horses in the study area as produced in this study seems to be the first of such documentation to the best of our knowledge in the area. Similar documentations of the distribution of Brucella infection in animals in Nigeria were those by Bertu, 2014;Kaltungo, (2018a) andBuhari et al (2020) who documented the distribution of Brucella infections in cattle and small ruminants in Kaduna, Katsina, Plateau and Sokoto States, Nigeria.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The documentation of geospatial distribution of B. abortus infection in horses in the study area as produced in this study seems to be the first of such documentation to the best of our knowledge in the area. Similar documentations of the distribution of Brucella infection in animals in Nigeria were those by Bertu, 2014;Kaltungo, (2018a) andBuhari et al (2020) who documented the distribution of Brucella infections in cattle and small ruminants in Kaduna, Katsina, Plateau and Sokoto States, Nigeria.…”
Section: Discussionsupporting
confidence: 78%
“…The finding of seroprevalence of Brucella among the sampled horses indicates that these horses might have been mixing with other domestic animals within the area as Kaltungo (2018aKaltungo ( , 2018b and Buhari et al (2020) have reported cattle, small ruminants and camels meeting at grazing and watering points and that such mixing might have facilitated transmission and spread of infections in these animal species. The fact that these horses had seroprevalence of Brucella means that there is high risk of infection by the grooms and even the horse owners who may ride them once in a while.…”
Section: Discussionmentioning
confidence: 89%
“…This and other sources of knowledge can also account for their knowledge on means of transmission of the diseases in animals, the occurrence of the disease in humans along with its signs and symptoms and methods of transmission in humans. Other workers like Kaltungo et al (2013); Kaltungo (2018a;Kaltungo 2018b) and Fadimu (2014) among others have similarly reported butchers and livestock owners' knowledge of zoonotic diseases. However, only a few of the butchers knew animals could acquire TB from humans and this can aggravate the situation, should any of them infected could spread the disease to his animals, especially those animals under fattening programmes and subsequently spread to the public through the carcasses after slaughter.…”
Section: Discussionmentioning
confidence: 90%
“…Tuberculosis (TB), has been reported in all -six geopolitical zones of Nigeria (Onunkwo et al 2003;Jenkins et al, 2011;Abubakar et al, 2014;Sani et al, 2015;Saidu et al, 2015;Saidu et al, 2017). The association of small ruminants with other animals in ownership holdings by pastoralists and farmers as well as the husbandry methods which predominantly involve extensive and semi-intensive methods usually increase the chances of small ruminants being infected with diseases seen mainly in cattle (Danbirni, 2016;Kaltungo, 2018a;Kaltungo, 2018b;Baba, 2019). The knowledge, attitude and practices of livestock owners in Nigeria, especially with regard to zoonotic diseases, seem to be low as reported (Buhari et al, 2015;Muhammad, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates a potential risk of infection for other animals should they graze in the same vicinity as these camels. Kaltungo (2018) and Kaltungo et al (2019) in a study on brucellosis in camels in Sokoto and Katsina States reported camels grazing and taking water in the same locations as cattle. The finding of sterile and calcified cysts could indicate long-standing of these cysts in the camels.…”
Section: Discussionmentioning
confidence: 99%